Jute - Microbiological and Biochemical Research (Plant Tissue Culture and Biotechnology, 2009)
The role of microorganisms obtained from jute (Corchorus spp.) in the retting of dry ribbons of jute was determined. Efficiency of fungus on retting of green ribbon and dry ribbon of jute was also examined. Attempt was made to determine the effect of nature of the harvested jute plants on the production of cuttings and improvement of their fibre quality, and the impact of stem-water ratio and retting of its top and basal parts separately on the quality of fibre. Distribution and activity of microbial population for jute retting and their impact on the water quality of jute growing areas of Bangladesh was also surveyed. Utilization and suitability of retting effluents as a fertilizer in vegetable crops production were also determined. Micrococcus spp. were identified as an accelerator of jute retting. Referring to the recent advancements made in isolating completed/partial genes controlling desirable traits, it is suggested to use the modern molecular technology not only to improve the quality of jute fibres but also bioengineer microbial flora to further reduce the retting time without sacrificing fibre qualities. Key words: Jute, Chemical composition, Bast fibre, Jute-cotton yarn, Transformation D.O.I. 10.3329/ptcb.v18i2.3651 Plant Tissue Cult. & Biotech. 18(2): 197-220, 2008 (December)